Predictors of HBsAg seroclearance in HBeAg-negative chronic hepatitis B patients treated with nucleotide analogs plus polyethylene glycol interferon - Peng, Yan; Ma, Mingzhe; Liu, Ting; He, Wenmin; Lin, Shutao; Zhong, Wa; Min, Xiaohui (Frontiers in Medicine, 2025)
IntroductionThe minority of the chronic hepatitis B (CHB) patients received polyethylene glycol interferon (PEG-IFN) combined with nucleotide analogs (NAs) can obtain hepatitis B surface antigen (HBsAg) clearance.MethodsIn order to find out the advantaged population, we retrospectively collected 122 CHB patients treated with NAs alone or NAs plus PEG-IFN for 48 weeks, who were admitted to Sun Yat-sen Memorial Hospital from 2019 to 2024.ResultsWe found HBsAg clearance rate in NAs plus PEG-IFN group was 40.98%, which was significantly higher than that in the NAs group. Thus, NAs plus PEG-IFN therapy served as a relatively ideal regimen and the patients received combined treatment were then incorporated for further analysis for searching efficacy predictors. Through using univariate and multivariate analysis, we confirmed the predictive value of HBsAg, alanine aminotransferase (ALT) at week 24, and ALT change values from baseline to week 24. The area under the receiver operating characteristic (ROC) curve of each indicators ranged from 0.663 to 0.982.DiscussionIn conclusion, our study verified the clinical value of NAs plus PEG-IFN for treating CHB patients. Moreover, for the first time, we found ALT change values from baseline to week 24 (dALT2) could act as a novel independent clinical efficacy predictors in the forementioned population.